Physical mapping by FISH of the DiGeorge critical region (DGCR): Involvement of the region in familial cases - Desmaze, C. (1993)
We describe the relative ordering, by fluorescence in situ hybridization, of cosmid loci and translocation breakpoints in the DiGeorge syndrome (DGS) critical region of chromosome 22. This physical map enables us to define a large region, commonly deleted in a majority of affected patients, and the smallest deleted region which, when lost, is sufficient to produce DGS. In four instances, a similar large deleted region is observed in a familial context. In these pedigrees, the deletion is encountered in one parent with mild features of the disease.